Swaziland Report on the Observance of Standards and Codes : Accounting and Auditing - World Bank (World Bank, Washington, DC, 2016)
The Report on Observance of Standards and Codes, Accounting and Auditing (ROSC A&A), requested by the Government of the Kingdom of Swaziland, contributes to development of a comprehensive plan that will strengthen the institutional framework that underpins accounting and auditing practices in the country. ROSC A&A program is a part of the joint World Bank-International Monetary Fund (IMF) initiative on assisting member countries to strengthen their financial system by improving capacity to comply with important internationally recognized standards and codes. The initiative covers twelve areas that relate to: (a) policy transparency; (b) financial sector regulation and supervision, Financial Sector Assessment Program (FSAP); and (c) market integrity. ROSC A&A relate to market integrity and specifically reviews and makes recommendations for strengthening the framework for education and training for accountants, the capacity and services of a professional accountancy organization, regulatory framework governing accounting and auditing practices, the applicable accounting auditing and ethics standards and the extent of their implementation, and the regulatory institutions and mechanism for monitoring and enforcing compliance with the standards.